Relevance of the Scenario in Cultural Events - Baxadirovna, Majitova Bibinaz (Research Parks Publishing LLC, 2023)
the article talks about the importance and role of the script in the organization and conduct of cultural events. The script is the most important part of the cultural event and the most powerful means of influencing the audience. That is, a creative weapon that affects the audience.